Prose for Senior Students: An Anthology of Short Stories and Essays - Gill, J.L. and Newell, L.H. (Toronto The Macmillan Company, 1960)
The short stories and essays contained in this book have been selected for students in their senior years of high school. In making their selection, the editors have attempted to choose stories and essays that combine both merit and interest.
Keywords: Reading